Two Case Report on Wrist Ganglion Treated with Scolopendrid Pharmacopuncture - Min-Seop Shin; Jin-Bok Lee; Beom-yong Song (Korean Pharmacopuncture Institute, 2010)
Object : This study was to investigate the clinical effect of Scolopendrid Pharmacopuncture on two patients suffering from Wrist Ganglion. Methods : We treated two patients suffering from Wrist Ganglion with both acupuncture and injection of Scolopendrid Pharmacopuncture. Then we measured the sizes of Wrist Ganglion and Visual Analogue Scale(VAS). Results and Conclusions : We found that the sizes of Wrist Ganglion of the two patients were significantly reduced. Moreover, the pain and discomfort of the wrists of the patients were reported to be reduced. So, we concluded that Scolopendrid Pharmacopuncture has an excellent effect on Wrist Ganglion. However, further studies are needed to investigate its exact effects.